ROLE OF VILLAGE OWNED ENTERPRISES (BUMDES) IN DESA TULABOLO EAST SUWAWA SUB-DISTRICT BONE BOLANGO COUNTRY - Riska Bouty; Imam Mashudi; Ismail Tahir (LP2M Universitas Bina Mandiri Gorontalo, 2022)
This research aims to find out the role of village-owned enterprises (BUMDesa)in community economic empowerment in Tulabolo Village, East Suwawa District ofBone Bolango Regency.This research method uses descriptive research with a qualitative approach. Datacollection techniques are used in this study through observation, interviews anddocumentation. The number of informants there are 5 people consisting of, thevillage head, the village secretary, bumdes manager and 2 people.The results of this study are seen in the principle of management of BUMDesdoes not run optimally, including: Cooperative principles.Directionless managementand the attitude of disrespecting each other's duties and main functions of fellowBUMDes managers. Participatory principle.The existence of BUMDes managers onthe management of business units that do not carry out their main duties causesfriction so as to damage the structure of the BUMDes container.EmancipatoryPrinciples. Emancipation between the village government, BUMDes administratorsand the village community is well established but the manager has not beenmaximally empowered by the presence of BUMDes containers. The principle oftransparency.Unclear in terms of administration and management of capital. ThePrinciple of Accountability. The board is no longer responsible for technically oradministratively managing BUMDes to the village government. SustainablePrinciples.Bumdes Inogaluma's administrators and activities are currently freezing.The main advice on the run is that the government pays attention that in providingincentives must be regulated in village regulations and in recruiters the managementof the back really pays attention to the science of education at its disposal.